PENGARUH CURRENT RATIO,DEBT TO EQUITY RATIO DAN RETURN ON INVESTMENT TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2016 - Ngatini Fajariyanti (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to analyze and understand (1) the influence of Current Ratio, Debt to Equity Ratio, Return on Investment simultaneously to Dividend Payout Ratio (2) the influence of Current Ratio to Dividend Payout Ratio (3) the influence of Debt to Equity Ratio to Dividend Payout Ratio (4) the influence of Return on Investment to Dividend Payout Ratio in automotive sub-sector and components listed in Indonesia Stock Exchange year 2011-2016. This research belongs to the type of correlational research. The population is all automotive sub-sector companies and components of 13 companies listed on the Indonesia Stock Exchange. The sample used in this study amounted to 4 companies. Method of data collection using documentation method, while data analysis technique use multiple linear regression analysis supported by classical assumption test consisting of normality test, multicolinearity test, heterokedastisity test, autocorrelation test besides supported also by f test and t test. The results showed that multiple linear regression equation for three predictors is DPR = -6,326 + 0,367CR-0,175DER + ε.